Pieces of eight : more archaeology of piracy - Ewen, Charles Robin; Skowronek, Russell K. (University Press of Florida, 2016)
Going back to the "Queen Anne's Revenge," La Salles's "La Belle," and adding the newest finds from Captain Kidd's "Cara Merchant of Quedagh" and Captain Henry Morgan's encampments, this volume reveals new discoveries and new ways of looking at the archaeology of pirates.